Rare earth element geochemistry and tetrad effects in fluorites: A case study from the Qahr-Abad deposit, Iran - Azizi, Mansour Rezaei; Abedini, All; Alipour, Samad; Niroomand, Shojaeddin; Sasmaz, Ahmet; Talaei, Babak (E Schweizerbartsche Verlagsbuchhandlung, 2017)
The Qahr-Abad fluorite deposit in western Iran is characterized by fluorites that mainly occur as veins, veinlets, and open-space fillings in dolomitic host rocks of the Triassic Elika Formation. Fluorites of different colours display conjugate convex and concave chondrite-normalized REE distribution patterns, have both positive and negative Eu anomalies and show non-CHARAC (non charge-radius control) behaviour of the Y/Ho, Zr/Hf, and Nb/Ta ratios. This means that fluorite is likely to have precipitated from fluids at different stages and/or of different compositions. The conjugate M- and W-type tetrad effects can be attributed to F-complexing of REE during fluorite formation, to the presence of clay minerals, and to fluid-rock interaction during fluorite precipitation. The correlation between T-3, (the size of the third tetrad effect) and the Eu anomaly in late and early stage fluorites, supports the hypothesis that there are different causes and origins for the tetrad effects and of the fluids. Y/Ho and Zr/Hf against T-3, diagrams show the non-CHARAC behavior of these pairs in the fluorites, probably caused by hydrothermal fluids originating from the magmatic system. High Y/Ho and Zr/Hf ratios in early stage fluorites may be due to precipitation from F-rich fluids, and low ratios in late stage fluorites may be attributed to CO32- rich hydrothermal fluids, or to interaction of Mg-bearing hydrothermal fluids with carbonate host rocks during long distance migration. Nb/Ta vs. T-3, diagrams indicate that two fluids of different compositions can be assumed to have been responsible for the development of the Qahr-Abad fluorite deposit. Early stage fluorites formed from a relatively high temperature and acidic, F-rich hydrothermal fluid, but late stage fluorites likely precipitated from a more evolved, low temperature solution during fluid-rock interaction processes.
Keywords: REE; tetrad effect; geochemistry; fluorite; Qahr-Abad; Iran